1991
DOI: 10.1121/1.400538
|View full text |Cite
|
Sign up to set email alerts
|

Envelope expansion methods for speech enhancement

Abstract: The last decade has seen increasing interest in techniques for the enhancement of digital speech signals. Significant gains have been made in terms of signal-to-noise ratio (SNR) and quality, but few techniques have produced improvements in intelligibility. A method for speech enhancement based on nonlinear expansion of the spectral envelope is presented. The expansion is consistent with both the long-term spectrum of the speech and with the probability that speech is present in a given sample. Objective SNR m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 0 publications
1
11
0
1
Order By: Relevance
“…Several spectral enhancement techniques have been tested using NH and hearing-impaired (HI) listeners in attempts to improve their speech understanding in noise (Baer et al, 1993;Bunnell, 1990;Clarkson and Bahgat, 1991;Franck et al, 1999;Lyzenga et al, 2002). In particular, Lyzenga et al (2002) used a spectral expansion scheme to enhance parts of the spectrum corresponding to vowel formants.…”
mentioning
confidence: 98%
“…Several spectral enhancement techniques have been tested using NH and hearing-impaired (HI) listeners in attempts to improve their speech understanding in noise (Baer et al, 1993;Bunnell, 1990;Clarkson and Bahgat, 1991;Franck et al, 1999;Lyzenga et al, 2002). In particular, Lyzenga et al (2002) used a spectral expansion scheme to enhance parts of the spectrum corresponding to vowel formants.…”
mentioning
confidence: 98%
“…Therefore, several investigations have been carried out to study the usefulness of envelope enhancement in improving speech understanding in the presence of noise in individuals with hearing impairment (Apoux et al, 2001;Clarkson & Bahgat, 1991;Fu & Shannon, 1998). However, the results of these studies were equivocal.…”
Section: Sumariomentioning
confidence: 97%
“…While amplitude compression was shown to have detrimental effects on speech intelligibility for normal-hearing (NH) and hearing-impaired (HI) listeners (Plomp, 1988;Fu and Shannon, 1999;van Buuren et al, 1999), moderate envelope expansion was found to be beneficial especially in adverse listening conditions (Clarkson and Bahgat, 1991;Fu and Shannon, 1999). Fu and Shannon (1999) reported a small decrease in speech intelligibility in quiet for the expansion of the envelope by a power law function.…”
Section: Introductionmentioning
confidence: 99%